(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The issue of artistic speech is a specific feature of the product of artistic creativity, a feature of the writer’s poetic skill. This article talks about artistic speech, its various artistic means and genres.